Evaluation of an anatomical syndesmosis classification - Bosserhoff, Niklas; Gablac, Hannah; Hoffmann, Michael (Journal of the Foot & Ankle, 2026)
Objective: To analyze geometric variations of the tibiofibular syndesmosis incisura fibularis to enhance understanding of its anatomical structure and propose a novel anatomical classification system. Methods: Retrospective analysis of 53 patients who underwent computerized tomography imaging of the ankle. Measurements were taken for various parameters of the incisura fibularis, including length, depth, angle, and fibular engagement. Injury status was taken into consideration. Results: Based on the incisura angle, a classification was established categorizing the incisura into three types: curved (IC, angle < 130°), normal (I0, angle 130°–160°), and shallow (IS, angle > 160°). Correlations between various parameters were identified. Additionally, significant differences in fibular engagement measurements were observed between uninjured (0.96 mm) and injured patients (0.28 mm; p = 0.017). Conclusion: Understanding anatomical variations of the incisura fibularis is crucial for optimizing surgical interventions in syndesmotic injuries. The St. Georg Classification provides a structured approach to guide orthopedic surgeons in creating individualized treatment protocols, reducing the risk of malreduction and improving patient outcomes. Further research is needed to explore the classification’s impact on injury patterns and long-term results. Level of Evidence III; Retrospective comparative study.